The Influence of Good Corporate Governance on Company Value in Jakarta Islamic Index Companies - Vera Oktari; Nanda Fito Mela; Arumega Zarefar (Politeknik Caltex Riau, 2018)
The goal of this study is to assess the effect of the Board of Commissioner, Independent Commissioner, and Audit Committee to company value. The population in this study was all companies in Jakarta Islamic Index as many as 30 companies. This study is using purposive sampling method, there are 15 companies that listed in Jakarta Islamic Index on 2012-2016 that meets the criteria of the sample. The data analyzed by using multiple regression. The study states that the Board of Commissioner does not have a significant influence on firm value. Independent Commissioner has a significant impact on the corporate value. Audit committee has a significant effect on firm value.